The role of reactive oxygen species and apoptosis in the pathogenesis of varicocele in a rat model and efficiency of vitamin E treatment - YALÇIN, AHMET SUHA; HAKLAR, GONCAGÜL; ÇAM, HAYDAR KAMİL (WILEY, 2004)
We investigated role of reactive oxygen species (ROS) and apoptosis in the pathogenesis of infertility in experimental model of varicocele. The protective effect of vitamin E was also examined. Three groups of rats were constructed as the first group had sham operation, experimental varicoceles were established by partial ligation of the left renal vein in later two groups. Third group had received vitamin E. Production of ROS was determined by chemiluminescence assay (CL). The in situ end labelling technique was utilized to investigate apoptosis. Tissue vitamin E levels were measured by high performance liquid chromatography. The differences between luminol enhanced CL levels of groups were not statistically significant. However, the difference between CL levels of lucigenin probe in left testicles of sham and varicocele groups were statistically significant (p = 0.0007). Similarly, the results of the third group receiving vitamin E significantly differed from the varicocele group (p = 0.0025). The difference of apoptotic index was also statistically significant between sham and varicocele groups (p = 0.0038). Although the values of apoptotic index detected in the vitamin E group were lower compared with the varicocele group, the difference was not significant. This study proposes that ROS production and apoptosis in the testicles were induced with experimental varicocele. Vitamin E had a protective role. An increased rate of apoptosis with experimental varicocele suggests a molecular alteration, which may involve ROS overproduction as the triggering mechanism. Consequently, this study indicates an association between varicocele and infertility at molecular level through stimulation of ROS and apoptosis.
Keywords: apoptosis; pathophysiology; reactive oxygen species; varicocele; TESTICULAR BLOOD-FLOW; TEMPERATURE; CELLS; SPERMATOZOA; PLASMA; MEN